Tuning colloidal gels by shear1. Issue 23 (21st June 2015) - Koumakis, Nick; Moghimi, Esmaeel; Besseling, Rut; Poon, Wilson C. K.; Brady, John F.; Petekidis, George
<x xml:space="preserve">Abstract</x> Using a powerful combination of experiments and simulations we demonstrate how the microstructure and its time evolution are linked with mechanical properties in a frustrated, out-of-equilibrium, particle gel under shear.